Analisis Kemampuan Pemecahan Masalah Matematis : Dampak Model Pembelajaran SAVI ditinjau dari Kemandirian Belajar Matematis - Murti, Evi Dwi; Nasir, Nasir; Negara, Hasan Sastra (Desimal: Jurnal Matematika, 2019)
This writing aims to see the effect of using the SAVI learning model on students' problem solving abilities. The type of writing is quantitative writing. The sampling technique used was randomized class. The data collection technique used is the essay test technique. The data analysis technique used is the two jaur anava test. Based on the hypothesis test obtained, the results show that there are influences of students with treatment using the SAVI learning model to improve mathematical problem solving skills in algebraic factorization material better than students with the treatment of learning using conventional learning both in general and in each category. the independence of students' mathematical learning. There is interaction between mathematical problem solving abilities of students who have high mathematical learning independence better than students who have moderate and low mathematical learning independence. While students who have mathematical learning independence are better than students who have low mathematical learning independence. In addition, there is no interaction between the treatment of learning and the category of self-reliance on students 'mathematical learning towards improving students' mathematical problem solving abilities.